REPOSITION OF THE UNIVERSAL DECLARATION OF HUMAN RIGHTS IN THE STATE LEGAL SYSTEM - Nurrohim Yunus; Refly Setiawan; Siti Ngainnur Rohmah (Al Qisthas Jurnal Hukum dan Politik, 2022)
The Universal Declaration of Human Rights (UDHR) is the foundational human rights declaration. The United Nations adopted it on December 10, 1948. The Universal Declaration of Human Rights is a global reference that establishes universal principles for achieving human rights. Although the Universal Declaration of Human Rights lacks official legal power, its fundamental concepts have become universal standards and are regarded as international law by many nations. Human rights have been codified in numerous international, national, provincial, and local/municipal legal texts. In this piece, the author employs a qualitative descriptive research methodology. It is said to be 'universal' because this right is stated to be a part of every human being's humanity, regardless of skin color, gender, culture, or religion; and it is said to be 'attached' because anyone possesses this right by virtue of his birth as a human being and not because of the grant of any authority institution. This privilege cannot be revoked by anyone because it is "attached." On the basis of the articles of all applicable Indonesian constitutions, it is possible to assert that the conceptualization of human rights in Indonesia has undergone a rigorous and protracted dialectical process. Incorporating human rights into the constitution demonstrates a commitment to upholding the law and human rights. In addition, different human rights provisions in the Indonesian constitution have been crafted to satisfy the needs and requirements for human rights protection in the personal, family, community, and national contexts.